Anthropometric parameters and leg power performance in fencing. Age, sex and discipline related differences - Ntai, A.; Zahou, F.; Paradisis, G.; Smirniotou, A.; Tsolakis, C. (Science & Sports, 2017)
Objective: The aim of this study was to compare anthropometric, body composition, and leg power performance in male and female, elite, and national fencers of all age competitive groups and discipline practiced. Subjects and methods: A total of 125 fencers (mean ± SD; age 20.6 ± 6.7 years, height 173.2 ± 9.2 cm and body mass 64.7 ± 4.7 kg) participated in this study. Anthropometric measurements were taken before participants performed squat, countermovement, drop, and standing log jump. Results: Significant differences were identified between male and female for height (177.6 ± 8.9 cm vs. 167.9 ± 6.2 cm, P < 0.001), body mass (70.4 ± 11.9 kg vs. 57.6 ± 7.0 kg, P < 0.001), arm span (181.8 ± 9.7 cm vs. 168.8 ± 7.2 cm, P < 0.001), leg length (88.9 ± 6.4 cm vs. 81.7 ± 4.3 cm, P < 0.001) and body mass index (22.2 ± 3.0 vs. 20.5 ± 2.1, P < 0.001) and for long jump (202.2 ± 34.7 cm vs. 167.4 ± 23.5 cm, P < 0.05), squat jump (26.5 ± 7.13 cm vs. 19.9 ± 4.00 cm, P < 0.05), counter movement jump (30.1 ± 7.4 cm vs. 21.7 ± 4.5 cm, P < 0.05), drop jump (28.4 ± 9.5 cm vs. 22.3 ± 6.4 cm, P < 0.05) and reaction strength index (0.90 ± 0.4 vs. 0.66 ± 0.3, P < 0.05), respectively. Significant differences in jumping performance were observed between the 14-17 years old and the > 20 years old group for long jump (179.2 ± 30.8 cm vs. 205.2 ± 33.9 cm, P < 0.05), squat jump (21.9 ± 5.3 cm vs. 26.2 ± 7.8 cm, P < 0.05), counter movement jump (25.1 ± 5.9 cm vs. 29.0 ± 8.6 cm, P < 0.05), drop jump (19.01 ± 7.0 cm vs. 25.2 ± 6.7 cm, P < 0.05) and reaction strength index (0.69 ± 0.35 vs. 0.96 ± 0.32, P < 0.05) and between the 18-20 years old > and the 20 years old group for long jump (174.0 ± 30.3 cm vs. 205.2 ± 33.9 cm, P < 0.05), squat jump (22.6 ± 6.1 cm vs. 26.2 ± 7.8 cm. P < 0.05), countermovement jump (24.9 ± 7.1 cm vs. 29.0 ± 8.6 cm, P < 0.05), drop jump (20.9 ± 6.8 cm vs. 25.2 ± 6.7 cm, P < 0.05) and reaction strength index (0.71 ± 0.4 vs. 0.96 ± 0.32, P < 0.05), respectively. Elite fencers performed better in squat (27.3 ± 7.1 cm vs. 22.9 ± 6.5 cm, P < 0.05), countermovement jump (30.5 ± 8.00 cm vs. 25.5 ± 7.2 cm, P < 0.05) and long jump (203.8 ± 38.9 cm vs. 183.2 ± 33.6 cm, P < 0.05) than national level fencers. Significant differences were observed for drop jump contact time between foil and epee groups (0.32 ± 0.01 ms vs. 0.28 ± 0.01 ms, P < 0.05), respectively. Conclusion: The observed differences in anthropometric measurements and leg power performance will facilitate the identification of the most suitable athletes and highlighted specific power abilities that could support the technical drills in competitive fencing.